The adenosine hypothesis of schizophrenia into its third decade: From neurochemical imbalance to early life etiological risks - Singer, Philipp; Yee, Benjamin K. (Frontiers in Cellular Neuroscience, 2023)
The adenosine hypothesis of schizophrenia was conceptualized about two decades ago in an attempt to integrate two prominent theories of neurochemical imbalance that attribute the pathogenesis of schizophrenia to hyperfunction of the mesocorticolimbic dopamine neurotransmission and hypofunction of cortical glutamate neurotransmission. Given its unique position as an endogenous modulator of both dopamine and glutamate signaling in the brain, adenosine was postulated as a potential new drug target to achieve multiple antipsychotic actions. This new strategy may offer hope for improving treatment, especially in alleviating negative symptoms and cognitive deficits of schizophrenia that do not respond to current medications. To date, however, the adenosine hypothesis has yet led to any significant therapeutic breakthroughs. Here, we address two possible reasons for the impasse. First, neither the presence of adenosine functional deficiency in people with schizophrenia nor its causal relationship to symptom production has been satisfactorily examined. Second, the lack of novel adenosine-based drugs also impedes progress. This review updates the latest preclinical and clinical data pertinent to the construct validity of the adenosine hypothesis and explores novel molecular processes whereby dysregulation of adenosine signaling could be linked to the etiology of schizophrenia. It is intended to stimulate and revitalize research into the adenosine hypothesis towards the development of a new and improved generation of antipsychotic drugs that has eluded us for decades.